Thermal, structural, textural and optical properties of ZnO/ZnAl2O4 mixed metal oxide-based Zn/Al layered double hydroxide. (5th September 2018) - Salih, Ethar Yahya; Sabri, Mohd Faizul Mohd; Sulaiman, Khaulah; Hussein, Mohd Zobir; Said, Suhana Mohd; Usop, Rohida; Salleh, Mohd Faiz Mohd; Ali Bashir, Mohamed Bashir
Abstract: Mixed metal oxides (MMO) with a homogenously distributed ZnAl2 O4 in ZnO network were prepared through a novel combination of co-precipitation and thermal treatment approaches using Zn/Al-layered double hydroxide (LDH) as precursor. The effect of thermal treatment temperature of Zn/Al-LDH for the formation of ZnO/ZnAl2 O4 -MMO was studied via their thermal, structural, textural and optical properties. The results reveal that the synthesized Zn/Al-LDH was advanced to ZnO/ZnAl2 O4 -MMO starting at 200 °C, while heat treatment at 400 °C resulted in the optimum BET surface area of 53 m 2 g −1 with formation of mesoporous structure. Furthermore, diffuse reflectance microscopy showed that there is more than one energy band gap of pristine Zn/Al-LDH, while samples treated at 200 °C and above demonstrated a single energy band gap with redshift from 3.3 to 3.21 eV. Photoluminescence (PL) analysis showed a quench in the PL spectra as the temperature increased to 400 °C, where the sample with the optimum surface area presents the highest I NBE /I DLE ratio of 0.78. A precise control of the thermal treatment temperature provides short pathways for preparing high BET surface area MMO-based materials.